¿Cómo incentivar la participación del alumnado? Experiencia de un proyecto piloto de traducción en la Universidad de Wrocław - Kuźnik, Anna (2015)
In the paper I present several didactic tools that contributed, accordingly to my experience, to motivate translation students to be an active and involved subjects in all the stages of the execution of a translation project, commissioned by two Polish companies from a tourist sector. These didactic tools are as follows: (1) qualitative surveys carried out with the aim of make a concrete decision or collect students’ opinions; (2) brain storming sessions and its tangible result: letters to our customers, containing questions about the commissions received; and (3) open discussion forum, with notes registered by me afterwards. All these tools were used in 2012, in my course of L1-L2 translation from Polish into Spanish, at a postgraduate level, at the University of Wrocław, Poland.
Keywords: herramientas didácticas; participación de los alumnos; formación mediante ejecución de servicios; proyecto de traducción; proceso organizativo